Pengembangan Model Latihan Keseimbangan Melalui Permainan Tradisional Engklek Untuk Peserta didik Kelas 1 di SD Negeri Bulusari 1 Kecamatan Tarokan Kabupaten Kediri - Efrin Arysurya Prasetya; Wasis Himawanto; Dwi Sulistyo Nugroho (JURNAL ILMIAH NUSANTARA, 2025)
This study discusses the influence of developing a balance training model through the traditional game of hopscotch (engklek) on the academic achievement of first-grade students at SD Negeri Bulusari 1, Tarokan District, Kediri Regency. The research employs a qualitative descriptive approach with a classroom action research (CAR) method. The research sample consists of 32 first-grade students at SD Negeri Bulusari 1, Tarokan District, Kediri Regency. The classroom action research was conducted following the stages of planning, implementation, observation, and reflection. The developed balance training model is based on the traditional game of hopscotch (engklek). Based on the research findings, the use of the balance training model combined with the traditional game of hopscotch proved effective in enhancing floor gymnastics learning abilities in the Physical Education subject for first-grade students at SD Negeri Bulusari 1, Tarokan District, Kediri Regency, in the 2024/2025 academic year. Indicators of success were identified through an increase in The mean academic performance ratings of the pupils, initially at 68.2 during the pre-cycle phase, rising to 70.2 in Cycle I, and further significantly increasing to 72.3 in Cycle II. Additionally, this effectiveness was also demonstrated by the improvement in the proportion of learning that is complete, from 71.8% in the pre-cycle to 81.3% in Cycle I, reaching a maximum completeness level of 100% in Cycle II